PEST- AND SNW-ANALYSIS OF THE USE OF LIQUID HYDROGEN AS A MOTOR FUEL IN AVIATION - Boichenko, Sergii; Chen, Linfei; Korovushkin, Vitalii; Biliakovych, Oleh (General Energy Institute of the National Academy of Sciences of Ukraine, 2025)
This article conducts a comprehensive PEST (Political, Economic, Social, Technological) and SNW (Strengths, Neutrals, Weaknesses) analysis on adopting liquid hydrogen as a motor fuel in the aviation industry. The urgency for sustainable aviation fuels is accentuated by the escalating environmental concerns and the aviation sector's significant carbon footprint. Liquid hydrogen, recognized for its high energy density and zero carbon emissions at the point of use, emerges as a promising alternative to conventional aviation fuels. Through a PEST analysis, the article examines the multifaceted external factors influencing the feasibility of liquid hydrogen in aviation, including supportive policies, economic considerations, societal attitudes towards green aviation, and the technological challenges and advancements in hydrogen fuel technologies. The SNW analysis delves into the intrinsic aspects of liquid hydrogen's application in aviation, highlighting its strengths such as environmental benefits and renewable production potential, its neutral factors that may neither significantly impede nor accelerate its adoption, and its weaknesses including storage and transportation challenges. The article concludes with strategic recommendations to mitigate the identified deficiencies, leverage strengths, and transform neutrals into opportunities for the widespread adoption of liquid hydrogen in aviation. This study aims to provide stakeholders in the aviation sector with insightful analyses to navigate the complexities of introducing liquid hydrogen as a sustainable aviation fuel, contributing to the broader goal of achieving carbon-neutral aviation.